ACESSO DO USUÁRIO À ASSISTÊNCIA FARMACÊUTICA NO MUNICÍPIO DE SANTO ANTÔNIO DE JESUS - BA - Silva, Tatiane de Oliveira (2008)
Study about access of the user of the Family Health Program (PSF) to the Pharmaceutical Assistance in the municipality Santo Antonio de Jesus BA. The objective are to discuss the process of the organization s Pharmaceutical Assistance and; to analyze the way how to configure this access of the user to the Pharmaceutical Assistance in the Family Health Unit. The references contain the process of the building of the Medicines Policy in Brazil; organization s Pharmaceutical Assistance and the user s access to this assistance, a possibility to be construction as a right citizenship. Qualitative research, in one perspective critical-analytical, and the research field are Family Health Unit on urban and rural areas. The subjectives were three groups: group I, key-informant (two); group II, health worker (six); and group III, users (13). The techniques of production dates were systematic observation, semi-structured interview, and documental analyzes. As date analyzes method was the hermeneutic-dialetics from which were elaborate two categories: Category 1 - Organization s Pharmaceutical Assistance in Santo Antonio de Jesus-BA: meetingns and disagreements between thinking and doing.; Category 2 User´s access of to the Pharmaceutical Assistance or access to drugs¿ A way to be reconstruct. In relation to organization s Pharmaceutical Assistance, this is demarcated by the action of selection, planning, acquisition, storage and dispensing, a reality are still under construction, which to happen on centralize way and, in spite of to involver works of the different areas, not process of the articulate way, diverging of the proposal team work that is necessary to this activity. As limitation of the process of the organization, we indentified the excess activities made by workers, both of coordination of the Pharmaceutical Assistance as those of the workers of the Family Health Unit; absence of a proposal or policy of continuing education for workers, in the perspective of the accountability and valorization of the work, develop by their. This limitation brings implications to access of the user to Pharmaceutical Assistance, to regard the following dimensions: availability, geographic, economic, functional and communicational. The units are geographically accessibly to users, which the difficult most evident are in the rural area. The municipality show constant problems of the supply, which can to create extras expense to users, with the purchase medicine or to left their vulnerable to the complication of the pathology to whom are porter and of the no constant use of the medicine. Moreover, relation with the users from reception until the dispensing of medicine, are destitute of communication and interaction between the subjectives and, consequently of attachment, reception and humanization necessary for the resolution of the health action. Therefore, we believe that to the transformation this reality , in order to ensure access to the Pharmaceutical Assistance with quality and integral health care, and for which it is understood beyond the availability of medicines, it s necessary a reconstruction of the way of to think and to make of subject who participate directly of organization of the action of the Pharmaceutical Assistance, managers, workers and users, breaking practice mechanized, impersonal, bureaucratic, and little communicative that their characterize.